Economic Development of German Federal States in Regard to their Labor Market in 1990-2012 - Parkan, Hubert; Szobi, Pavel, 1983-; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The ongoing debate around a successful reunification process is dividing Germany, not only geographically but also socio-economically and politically. There have been some remarkable achievements during the reunification, especially during the first years, but the period 1990-2012 has also seen some negative developments. Analysis is based mainly on databases from the German Socio-Economic Panel (GSOEP), as well as other administrative data sources such as the Deutsche Institut for Wirtschaft (DIW). In examining and comparing the roles of demographic changes, productivity, the implementation of active labor market policies (ALMPs), labor participation, unemployment, education, the gender gap, and wage inequality, we analyze the development of the german labor market by its main determinants, in order to conclude whether the German government has succeeded in the reunification of East and West Germany.
Vedoucí práce: Pavel Szobi
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses